Development of Political Science Education and Nigeria’s Experience - Alkasim , Idris Alhassan; Sufi, Kabiru Sa’id (Kashere Journal of Politics and International Relations, 2023)
The objective of this paper is to explain the conceptual meaning and relevance of political science education as a discipline in global politics and Nigeria in particular. The study also traced the origin, historical antecedence as well as changing dimension in the development of Political Science as a discipline. The paper also explained some teaching methods relevance to Political Science as a discipline that covers different forms of specializations in politics such as political theories, political philosophy, political ideologies, comparative politics, public administration, political economy, conflict and conflict resolution, international relations and international organizations. The authors in this study identified some challenges encountered by Nigerian Political Science Teachers in both post Primary and Tertiary Institutions (colleges and universities). This paper adopted the descriptive research design method in examining Political Science Education in Nigeria. Methodologically, the study also adopted secondary sources of data collection and used functionalist theory culled from sociology as theoretical framework that offered explanations on the relevance of political science education in Nigeria. Content analysis is used in the paper to explain the findings of this study which establish positive facts in justifying the need for Political Science Education in Nigeria. Conclusively, the study made some recommendations such as national curriculum review by making political science a compulsory course/subject for all disciplines, field trip/excursion as well as in cooperating Information and Communications Technology (ICT) in teaching and learning Political Science subject for quicker realization of Nigeria’s national policy in education.